Pedagogical Practices in the Production of the Third-Person Singular Morpheme - Garita Gómez, Deykel Dyalá (2023)
Spaced Learning is implemented to prompt oral production of the third-person singular –s by Spanish EFL learners. This quantitative study involved three experimental groups and a control group. The experimental groups received differentiated instruction (form-focused, meaning-focused, and a combination of both) in which the technique is embedded. The data were coded and analyzed with the obligatory occasion analysis method and an ANOVA test. Results show that Spaced Learning combined with form-focused and meaning-focused instruction prompted the oral production of the morpheme. Consequently, it is recommended to use, but not complement, the tenants of each instruction in the EFL classroom.